The The Impact of Annual Report Readability on Agency Costs: Internal Control as Moderating Variable - Tarjo Tarjo (STIE Malangkucecwara, 2022)
This examination looks at the impact of yearly report comprehensibility on organization costs with inward control as a directing variable. This examination was directed at assembling organizations recorded on the Indonesia Stock Exchange in the 2014-2017 period. The populace utilized in this investigation added up to 142 organizations, and after the determination of tests with purposive examining methods got, 44 assembling organizations would be utilized as tests in this examination. The insightful technique in this examination utilizes the different straight relapse test with Moderate Regression Analysis (MRA). The aftereffects of this investigation show the clarity of yearly reports influence office costs, which implies the higher the degree of yearly report coherence, the higher organization costs looked by investors, the inward control reinforces the impact of yearly report lucidness on office costs, which implies that with inner control can diminish the impact of report intelligibility yearly along these lines lessening office costs.